0918 Chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids (CLIPPERS): no evidence for antibodies to neuronal surface antigens. Issue 3 (9th February 2012) - Maddison, P; Gozzard, P; Jaspan, T
Abstract : The recently described central nervous system inflammatory disorder, CLIPPERS, (chronic lymphocytic inflammation with pontine perivascular enhancement responsive to steroids) is a condition characterised by brainstem clinical features responsive to steroid treatment in which patients typically exhibit distinct symmetrical curvilinear gadolinium enhancement principally within the brainstem on MRI. Neuropathological findings of lymphocytic white matter perivascular infiltrate, coupled with a favourable response to immunosuppression have suggested an immune-mediated pathogenesis, although the cause remains unknown. Given the relapsing nature of this perivascular inflammatory disorder mirroring the use of immune therapies, we looked for evidence of antibodies to neuronal surface antigens that could be pathogenic, or act as biomarkers of CLIPPERS. We studied a patient with the typical clinical and radiological features of CLIPPERS but failed to demonstrate evidence of antibodies to neuronal surface antigens: indirect immunofluorescence performed on monkey cerebellum sections did not show anti-neuronal binding; and incubation of live unpermeabilised cells from cerebellar neuronal cultures with the patient's serum failed to show binding to the granule cell processes. It is possible that CLIPPERS could be mediated by other organ-specific antibodies to perivascular antigenic targets in the central nervous system, or alternatively a predominantly cell-mediated immune process.